Replay of episodic memories in the rat - Panoz-Brown, Danielle (Curr Biol, 2018)
Panoz-Brown et al. show that rats remember a stream of multiple episodes and the order in which they occur by engaging hippocampal-dependent episodic memory replay. They conclude that rats remember the order of events using episodic memory replay and that replay is part of long-term memory, resistant to interference, and hippocampal dependent. [Image: see text]